(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the necessary aspects of the design of lessons, the analysis of the teaching process, learning outcomes, teaching students to think, teaching creative analysis of knowledge, the transformation of acquired knowledge into skills. creation of a methodical system, important aspects of design in the acquisition of the content of knowledge and skills to be acquired by students, and as a result of these aspects a clear basis for students to choose their own path of learning, which - Involvement of professional needs and aspirations in the design of the educational process, the paradigm of person-centered education, the teacher in the design of training, first of all, the analysis of the teaching process, learning outcomes, independent students to teach thinking, independent reading, creative analysis of knowledge, to turn the acquired knowledge into skills to create a methodical system, to develop the content of knowledge, skills and abilities that students should acquire, to organize students’ learning activities and training exercises using the created methodical system and the content of educational data the purposeful selection of organizational forms of cognitive activity for children and the content of its implementation are explained